ECOLOGIA DE HEDYOSMUM BRASILIENSE MART. EX MIQ. (CHLORANTHACEAE): SUBSÍDIO PARA CULTIVO E MANEJO SUSTENTÁVEL - Zaniolo, Solange Ribas (Scientia Agraria, 2003)
The growing demand for medical remedies requires better understanding of the basic ecology of plants that supply the remedies, thus providing the theoretical basis for sustainably cultivating such plants. The goals of this study were to provide ecological information for the medicinal shrub Hedyosmum brasiliense Mart. ex Miq. (Chloranthaceae). This thesis is organized in seven chapters, all based on data collected from the Volta Velha Reserve (26°04' S, 48° 38' W), (tapoá, SC during 3 years (1998, 1999 and 2000). Detailed description of species and geoclimatic, soils and historic aspects of this place is presented in the chapter 2. Chapter 3 describes population structure and dynamics: plant height, crown area, growth, survival and sex ratio were studied. The continuous distribution and relatively rapid growth indicate that this shrub is regenerating in situ with a very high annual survival rate, hence showing promise as a sustainable source of medicinal compounds. In chapter 4 the phenology of this shrub was studied during 22 months (September 1998 to July 2000). Leaf, flower and fruit production were observed in 36 randomly selected individuals. This shrub species is evergreen with constant leaf production. All individuals flowered in both years, beginning in the drier month (August), with male plants flowering about a month before female plants. Fruit maturation began during the hot and wet period (January) and the fruiting period lasted for five months. Phenological patterns in this shrub were regular, consistent among plants and over the two years of the study. In chapter 5, humidity and light, and their possible interations, on germination rates were examined by placing seeds in two humidity regimes (10 and 20 ml H2O/gerbox), and four light regimes (white, red, far-red, and dark). Possible interactions between soil type and moisture content were examined with two soil types (soil and vermiculite) and four moisture levels (1/3, 2/3 and full field capacity, and saturation). Low germination rate in far red light is an indication that the plant is a pioneer species. The higher germination rates in soil at 1/3 capacity suggests that additional characteristics within the soil besides moisture may be important in germination. Also, saturated soils do not reduce seed viability, which is important for plant species found in saturated soils. Leaf structures were studied in Chapter 6 to aid in quality control of this medicinal species. Anatomical analyses were of mature leaves. Lamina were analysed at the leaf center on the level of its midrib. Laterocytic and large stomata, presence of glandular epidermal cells, undiferentiaded mesophyll, sclereids, hydathodes in the lamina and ducts in the petiole are characteristics typical this species and that are useful to test the possible admixture of others products. Chapter 7 provides a synthesis of these results, in order to provide a series of considerations and recommendations for the production and sustainable use of this plant.